STUDY OF GUT MICROBIOTA ALTERATIONS IN ALZHEIMER’S DEMENTIA PATIENTS FROM KAZAKHSTAN - Kaiyrlykyzy, Aiym; Kozhakhmetov, Samat; Babenko, Dmitriy; Zholdasbekova, Gulnaz; Alzhanova, Dinara; Olzhayev, Farkhad; Baibulatova, Aida; Kushugulova, Almagul R.; Askarova, Sholpan (Scientific Reports, 2022)
We have investigated the diversity and composition of gut microbiotas isolated from AD (Alzheimer’s disease) patients (n = 41) and healthy seniors (n = 43) from Nur-Sultan city (Kazakhstan). The composition of the gut microbiota was characterized by 16S ribosomal RNA sequencing. Our results demonstrated significant differences in bacterial abundance at phylum, class, order, and genus levels in AD patients compared to healthy aged individuals. Relative abundance analysis has revealed increased amount of taxa belonging to Acidobacteriota, Verrucomicrobiota, Planctomycetota and Synergistota phyla in AD patients. Among bacterial genera, microbiotas of AD participants were characterized by a decreased amount of Bifidobacterium, Clostridia bacterium, Castellaniella, Erysipelotrichaceae UCG-003, Roseburia, Tuzzerella, Lactobacillaceae and Monoglobus. Differential abundance analysis determined enriched genera of Christensenellaceae R-7 group, Prevotella, Alloprevotella, Eubacterium coprostanoligenes group, Ruminococcus, Flavobacterium, Ohtaekwangia, Akkermansia, Bacteroides sp. Marseille-P3166 in AD patients, whereas Levilactobacillus, Lactiplantibacillus, Tyzzerella, Eubacterium siraeum group, Monoglobus, Bacteroides, Erysipelotrichaceae UCG-003, Veillonella, Faecalibacterium, Roseburia, Haemophilus were depleted. We have also found correlations between some bacteria taxa and blood serum biochemical parameters. Adiponectin was correlated with Acidimicrobiia, Faecalibacterium, Actinobacteria, Oscillospiraceae, Prevotella and Christensenellaceae R-7. The Christensenellaceae R-7 group and Acidobacteriota were correlated with total bilirubin, while Firmicutes, Acidobacteriales bacterium, Castellaniella alcaligenes, Lachnospiraceae, Christensenellaceae and Klebsiella pneumoniae were correlated with the level of CRP in the blood of AD patients. In addition, we report the correlations found between disease severity and certain fecal bacteria. This is the first reported study demonstrating gut microbiota alterations in AD in the Central Asian region.
Keywords: Type of access: Open Access; ALZHEIMER’S DISEASE; microbiota; patients; dementia; Kazakhstan